Partial Least Squares Path Modelling of the Impact of National Cultures on Organisational Justice of Malaysian Assessment Centre - Mohd Hanafiah, Ahmad; Mohd Rashid, Ab Hamid; Noor Azlinna, Azizan (2015)
Assessment centres (AC) are a popular technique used in Human Resource Management which involves multiple assessment processes, where a group of participants takes part in exercises and is observed by a team of assessors who evaluate each participant against a number of predetermined, job-related behaviours. Although scholars explained that the success of this approach is due to its versatility and adaptability to the different purposes of the AC, as well as to cultural, societal, and organisational requirements, however, literature search shows that there has been very limited research carried out in the field of ACs to support these suggestions. Therefore, this study aims to respond to this research gap and contribute to the body of knowledge in this area by exploring the implementation of ACs in Malaysia, as an example of an Eastern, and developing country. Using an organisational justice theory, this study aims to explore how the national culture may influence the design and implementation of ACs in Malaysian public sectors. Structural Equation Modelling with partial least squares (PLS) estimation was applied to data obtained from 302 Administrative and Diplomatic Officers in various ministries in 2014. This data gathered information on the respondents’ demography and feedback on National Culture Dimensions (Collectivism and Relationship Preferences, Power Distance and Preference of Hierarchy, and Communication Context). The researcher also obtained data related to Organisational Justice (Procedural Justice - Structural Aspect, Information Sharing and Interpersonal Treatment, and Distributive Justice). Finally, data related to the outcome of the ACs (Attitude towards ACs, Affect and Recommendation) have also been collected. Eleven hypotheses were tested, and from the modelling analysis results, it showed Collectivism and Relationship Preferences and Communication Context showed a positively significant relationship at a two-tailed test in influencing the perceived of justice and acceptance of ACs. Meanwhile, Power Distance and Preference of Hierarchy showed non-significant paths on the Interpersonal Treatment and Structural aspect. In addition, Information Sharing also showed non-significant path on the attitude towards ACs. In conclusion, the findings indicated that Collectivism and relationship Preferences and Communication Context are the most influential cultural factor in influencing perception of justice and acceptance of ACs. The results also suggest that Malaysians are no longer a society that sees Power Distance and Preference of Hierarchy as one of the important cultural dimensions that will influence the design and implementation of management practices including ACs.